Engineering societies in the agents world : first international workshop, ESAW 2000, Berlin, Germany, August 21, 2000 : revised papers - Omicini, Andrea, 1965-; Tolksdorf, Robert, 1965-; Zambonelli, Franco, 1966- (Lecture notes in computer science ;)
This book constitutes the thoroughly refereed post-proceedings of the First International Workshop on Engineering Societies in the Agents World, ESAW 2000, held in Berlin, Germany in August 2000. The 10 revised full papers presented were carefully reviewed and selected for inclusion in the book; they are organized in topical sections on emerging issues in multi-agent systems engineering, coordination models and technologies for multi-agent systems, and methodologies and tools.